Statistical Literacy: A Preliminary Research to Identify Student's Level in Solving AKM Problems Based on Watson Category - Setio, Agus; Baiduri, Baiduri (Journal of Teaching and Learning Mathematics, 2023)
Literacy is essential in preparing for 21st-century life and the significant data era. At the very least, people need the ability to process, analyze, read, and use the data to make decisions. This ability is known as statistical literacy. The students' statistical literacy must be diagnosed well for appropriate learning improvements. This study is qualitative research with a quantitative descriptive approach; the instruments used are AKM (Asesmen et al. - Minimum Competence Assessment) problems and Watson's statistical literacy category. The respondents were 187 students from six schools with different statuses (three state and three private schools) with different abilities (two high-level schools, two medium-level schools, and two low-level schools). The results obtained: there are no students at level 1; 3.07% of students are at level 2; 8.82% 0f students at level 3; 14.84% of students are at level 4; 55.61% of students are at level 5, and 17.65% of students gain level 6. Based on the result, it is evident that the students' statistical literacy spread to several levels. Most of the students are in level 5, and a few can gain the sixth level, but still, there are several students at the third level, even the second level. Those data can be used as preliminary data to improve statistical learning methods and teaching materials and for further research, especially about why and how to increase students' statistical literacy